Unraveling the effects of tropical cyclones on economic sectors worldwide - Kunze, Sven (Discussion paper series, 2017)
Schlagwörter: Tropical cyclones; sectoral economic growth; environment and growth; natural disasters; input-output analysis
Keywords: Graue Literatur